THE IMPACT OF RELIGIOUS COMMITMENT OF BASHKORTOSTAN YOUTH ON THEIR ATTITUDE TOWARDS REPRESENTATIVES OF DIFFERENT CONFESSIONAL AFFILIATIONS - Salikhova, Elvina; Mukhtasarova, Elvira; Idrisova, Elina; Khaliulina, Aigul (Revista Inclusiones, 2020)
The article discusses the theoretical foundations of studies in linguistics, ethnopsychology, intercultural communication, sociolinguistics, and psycholinguistics, and also addresses the problem of ‘religion-man-ethnos-language’ in modern society. The subject of the study is represented by the sociological surveys, conducted by the authors and other specialists, and by the data of sociopsycholinguistic experiments. The object of scientific study was the characterization of the influence of the certain degree of religious commitment manifested by the youth of the Republic of Bashkortostan in their attitude to representatives of other confessional affiliations. The presented study employed the methods of descriptions, observation, questionnaire, comparison, and analysis of the survey results. Under the denomination, the authors understood the totality of religious communities that are united by the identity of creed and spiritual practices. The religion was comprehended as the spiritual and practical connection between people that arise based on a common belief in higher values. Religiosity was considered as the social quality of an individual or group of people, the degree of which is determined by the quantity and quality of existing ideas about religion and the constant need for their expansion, as well as the thoroughness and frequency of fulfilling religious orders. Religiosity was studied by the main parameter - religious consciousness, with particular attention to certain issues related to the religious behavior of the younger generation. The scientific novelty of the study refers to the consideration of the peculiarities of the manifestation of Bashkortostan youth ethnoreligious identity in a synchronous aspect. Empirical data are given; a conclusion is made on the ambiguity of the analyzed representations. Based on the theoretical analysis of literature and survey data, the authors recognized that, depending on the degree of religious commitment, questions of the attitude of modern youth of the Republic of Bashkortostan to representatives of different religious affiliations are currently open and require careful study.